2022
DOI: 10.1177/20552076221076927
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infodemic and digital health literacy in vulnerable populations: A scoping review

Abstract: Background People from lower and middle socioeconomic classes and vulnerable populations are among the worst affected by the COVID-19 pandemic, thus exacerbating disparities and the digital divide. Objective To draw a portrait of e-services as a digital approach to support digital health literacy in vulnerable populations amid the COVID-19 infodemic, and identify the barriers and facilitators for their implementation. Methods A scoping review was performed to gather published literature with a broad range of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 54 publications
1
69
0
5
Order By: Relevance
“…There is a growing amount of research on the impact of social media on how people responded to the COVID-19, and other important events of our times (Choukou et al, 2022). The present study confirms that this research is valuable.…”
Section: Sources Of Informationsupporting
confidence: 85%
“…There is a growing amount of research on the impact of social media on how people responded to the COVID-19, and other important events of our times (Choukou et al, 2022). The present study confirms that this research is valuable.…”
Section: Sources Of Informationsupporting
confidence: 85%
“…This study identified the characteristics of that vulnerable population and proposes the following measures to target them. Digital health or eHealth literacy can improve netizens’ capacity to search, compare, and take the best advantage of web-based information [ 73 ]. The government should establish programs to improve netizens’ eHealth literacy and strengthen their capacities to obtain, read, understand, and assess health care information so that they can use web-based COVID-19 information appropriately [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the C19 pandemic, telemedicine played a very important beneficial role, as it eliminated the risk of infecting the population requiring treatment or regular medical check-ups, facilitated access to information and identification of the health status of the quarantined population, facilitated multidisciplinary interventions, with medical teams from various parts of the world, in order to exchange experience and establish optimal solutions [ 131 , 132 ]. Therefore, many areas around the world, such as China, USA, and Australia, have established national telemedicine centers and regulated a series of measures to establish a legislative framework [ 133 , 134 , 135 , 136 , 137 , 138 ].…”
Section: Medical Staff Protectionmentioning
confidence: 99%